PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP HARGA SAHAM DI BEI TAHUN 2005 – 2010 - Dina Agustina Harahap (Jurnal Ekonomi Pembangunan, 2012)
To the effect research is subject to be know stock price reflect point of a firm. If firm reaches good achievement, therefore that firm stock will there are many hankered by investors. Good achievement that reached by perusahan can be seen in financial statement that dipubuikasikan by firm.   analisis's tool that is utilized on this research utilizes analisis bifilar regression.  Result observationaling to point out that capital Profitability variable memilki's sell growth having for to stock price partially with signifkan's zoom (0,000 and 0,000) meanwhile Capital Structure with level signifikan (0,048) are not influential to Textile stock price 2005 2010.